Empagliflozin's role in early tubular protection for type 2 diabetes patients - Chuangbiao Zhang; Weiwei Ren; Xiaohua Lu; Lie Feng; Jiaying Li; Beibei Zhu (BMC, 2024)
Abstract Background Patients with type 2 diabetes often face early tubular injury, necessitating effective treatment strategies. This study aimed to evaluate the impact of the SGLT2 inhibitor empagliflozin on early tubular injury biomarkers in type 2 diabetes patients with normoalbuminuria. Methods A randomized controlled clinical study comprising 54 patients selected based on specific criteria was conducted. Patients were divided into an intervention group (empagliflozin, n = 27) and a control group (n = 27) and treated for 6 weeks. Tubular injury biomarkers KIM-1 and NGAL were assessed pre- and post-treatment. Results Both groups demonstrated comparable baseline characteristics. Post-treatment, fasting and postprandial blood glucose levels decreased similarly in both groups. The intervention group exhibited better improvements in total cholesterol, low-density lipoprotein, and blood uric acid levels. Renal function indicators, including UACR and eGFR, showed greater enhancements in the intervention group. Significant reductions in KIM-1 and NGAL were observed in the intervention group. Conclusion Treatment with empagliflozin in type 2 diabetes patients with normoalbuminuria led to a notable decrease in tubular injury biomarkers KIM-1 and NGAL. These findings highlight the potential of SGLT2 inhibitors in early tubular protection, offering a new therapeutic approach.